Verbal applicatives in Nuuchahnulth - Steriopolo, Olga (ZAS Papers in Linguistics, 2015)
In this article, I provide a description and analysis of the morphemes čiɫ 'do to', ḥta 'do towards' and cḥin 'do for' in the Southern Wakashan language Nuuchahnulth (nuučaan̓uɫ). I argue that these morphemes are verbal applicatives that add a non-core argument to the thematic structure of a verb. Verbal applicatives in Nuuchahnulth are interesting to investigate because they exhibit typologically unique behaviour that has never been studied before. Applicatives are traditionally considered functional elements whose only purpose is to add an indirect object to the argument structure of the verb (Pylkkanen 2002:17). Nuuchahnulth is the only known language that productively uses independent verbs for this purpose. Nuuchahnulth is an indigenous language of Canada spoken in the province of British Columbia. It consists of 14 major dialects, most of which have never been studied. All of these dialects are now highly endangered and urgently need to be documented.